Linguistic and Textual Structure Representation in Biographical Writing: Insights from BIPA Learners - Yohana Monika Masing Wato; Ida Widia; Mochamad Whilky Rizkyanfi; Vinsensius Bawa Toron; Aderita Mariana Takeleb (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The study aims to comprehensively map the ability of BIPA students from Timor-Leste in writing biographical texts, while identifying their strengths and weaknesses in several key aspects: clarity of content, writing structure, creativity and language style, adherence to theme, and spelling and grammar accuracy. Methodology: Data were collected through a biographical writing task, which was assessed using a specially designed rubric. A mixed-method approach was applied: quantitative analysis was used to examine the distribution of ability levels across categories, while qualitative analysis explored detailed patterns of strengths and weaknesses for each aspect. Main Findings: The findings show that most students achieved a medium level for clarity of content (57.5%) and writing structure (60%). However, creativity (65% low) and spelling and grammar (52.5% low) emerged as the main challenges. Specific difficulties were identified in the formation of derived words, the use of temporal conjunctions, and the construction of complex sentences. Novelty/Originality of this study: This study places biographical writing as an instrument for diagnosing the writing skills of BIPA students in the sociolinguistic context of Timor-Leste, a domain that is rarely explored. This approach allows for a more detailed mapping of students’ strengths and weaknesses rather than just measuring final scores for pedagogical intervention. The implications suggest that BIPA teachers should prioritize fostering grammatical cohesion, enhancing creativity, and refining the reorientation section of biographical texts. The implementation of a scaffolding model progressing from guided examples to independent production is recommended to systematically develop students’ writing competence.